Teacher Professionalism in the Perspective of Philosophy of Education: A Systematic Literature Network Analysis - Septi, Elni; Kristiawan, Muhammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
Teacher professionalism has long been understood not merely as technical skills but as ethical, epistemological, and ontological practice rooted in philosophy of education. However, previous studies tend to be fragmented between empirical investigations and philosophical reflections. This study employs SLNA, integrating systematic review and bibliometric analysis, to map the research landscape on teacher professionalism and examine its philosophical foundations. Literature searches were conducted through Scopus using a structured strategy, yielding 249 articles, of which 138 met inclusion criteria. Bibliometric analysis using VOS viewer identified four major thematic clusters: pedagogical competence, professional integrity, continuous development, and social responsibility. Temporally, research themes evolved from early focus on technical skills toward ethics, professional epistemology, and existential meaning of teaching. Systematic review findings indicate that teacher professional development interventions are positively associated with conceptual understanding, scientific process skills, and student engagement, with aggregated standardized effect estimates (Hedges’ g ≈ 0.67), indicating moderate-to-large positive impact. Philosophical analysis reinforces these findings by highlighting teachers' roles as moral agents, epistemic subjects, and ontological entities within educational praxis. SLNA integration demonstrates that teacher professionalism cannot be fully understood from empirical dimensions alone but requires strong philosophical foundations to address 21st-century educational challenges. This study provides comprehensive landscape of teacher professionalism while underscoring necessity of synthesizing empirical evidence and philosophical reflection as basis for advancing educational theory, policy, and practice.